Voltage-Gated Ca2+-Channel α1-Subunit de novo Missense Mutations: Gain or Loss of Function – Implications for Potential Therapies - Striessnig, Jörg (Frontiers in Synaptic Neuroscience, 2021)
This review summarizes our current knowledge of human disease-relevant genetic variants within the family of voltage gated Ca2+ channels. Ca2+ channelopathies cover a wide spectrum of diseases including epilepsies, autism spectrum disorders, intellectual disabilities, developmental delay, cerebellar ataxias and degeneration, severe cardiac arrhythmias, sudden cardiac death, eye disease and endocrine disorders such as congential hyperinsulinism and hyperaldosteronism. A special focus will be on the rapidly increasing number of de novo missense mutations identified in the pore-forming α1-subunits with next generation sequencing studies of well-defined patient cohorts. In contrast to likely gene disrupting mutations these can not only cause a channel loss-of-function but can also induce typical functional changes permitting enhanced channel activity and Ca2+ signaling. Such gain-of-function mutations could represent therapeutic targets for mutation-specific therapy of Ca2+-channelopathies with existing or novel Ca2+-channel inhibitors. Moreover, many pathogenic mutations affect positive charges in the voltage sensors with the potential to form gating-pore currents through voltage sensors. If confirmed in functional studies, specific blockers of gating-pore currents could also be of therapeutic interest.